Impact of combined fixed-dose formulations in Helicobacter pylori eradication on incidence rate of gastric cancer in Ukraine from 2014 to 2021 - Y.O. Protas; O.V. Makarenko; R.V. Duka (Medičnì Perspektivi, 2025)
A worldwide decrease in the incidence of gastric cancer and its most common form, adenocarcinoma, has long been observed. Helicobacter pylori (H. pylori) is a causative carcinogen for gastric adenocarcinoma. Triple and quadruple regimens for H. pylori eradication have been well identified and established. Aims of the research: this article aims to evaluate trends in the administration of combined drug therapy for H. pylori eradication and how this can impact gastric cancer rates in Ukraine.Defined daily doses (DDD) of the combined drugs for H. pylori eradication (years 2014-2020), gastric cancer, and gastric adenocarcinoma incidence rates in Ukraine from 2014 to 2021 were calculated and analyzed annually per 100,000 of inhabitants. The number of DDDs of the combined drugs used in H. pylori eradication increased by 27.28% (p<0.0001). The incidence of gastric cancer decreased by 26.56% (p<0.0001) from 2014 to 2021. Gastric adenocarcinoma was the most common form of gastric cancer comprising 94.56% (93.04–96.56%, 95% CI) of all cases. In Ukraine, the consumption of combined drugs for H. pylori eradication increased from 2014 to 2020, while the incidence of gastric cancer and gastric adenocarcinoma decreased from 2014 to 2021. Gastric adenocarcinoma is the most common form of gastric cancer in Ukraine. Use of these drugs might contribute to the decrease in gastric cancer incidence rate. These trends reflect global patterns.